Huang Po and the Dimensions of Love (Book collections on Project MUSE., 2012)
In Huang Po and the Dimensions of Love, poet Wally Swist blends themes of love and epiphany to lead readers into a more conscious interaction with the world around them. These ethereal poems call upon a spirituality unfettered to any specific religion, yet universal and potent in its scope, offering a window through which life can be not only viewed but also truly experienced. This luminescent collection illustrates the joys to be found in the everyday world and the power of existence. Unveiled here are the twin edges of love and madness; the quiet mysteries and revelations o.